The Development of University Technology and Innovation Incubators to Respond to the Needs of the Modern Economy - Mashau, Pfano; Fields, Ziska (International Journal of Criminology and Sociology, 2022)
The growing demand for technology and innovation has created a pressing need for higher education institutions in South Africa to be involved in the development of the country. The National Development Plan 2030 challenges higher education institutions to actively participate in developing and sustaining the well-being of South Africa. The article emphasises that sustainable development can be achieved through university activities, in which university technology and innovation incubators play a role; hence the need for such incubators. Transition to a knowledge society entails the university and other knowledge institutions acting in partnership with industry and government, and even taking the lead in joint initiatives. Therefore, this article recommends that technology entrepreneurs and innovation should be developed through universities, both in South Africa and in Africa as a whole, as suggested by the triple helix theory.